Benefits to processor load for quadrature baseband versus radio frequency demodulation algorithms - Ndovi, Lusungu (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--Stellenbosch University, 2008.